European Union and Southeastern Europe: A clash of the principle of conditionality and the regional approach - Wichmann Nina (Međunarodni Problemi)
The European Union in June 2003 has made it very clear that the principle of conditionality and the regional approach will be the prime instruments of the EU in South East Europe. The author in this article investigates if some of the stipulations about these instruments do hold. The central stipulation is that only in tandem would the principles provide for stability. The author contents that it remains doubtful whether the proclaimed compatibility of the two approaches is given. Rather, competition seems to exist between them. However, if this rivalry is really given and yet the combination of the two principles remains to be the flagship policy of the EU, this may be counter-effective for reaching the desired stabilization and democratization of the region.